An orbital principle to design P2-NaxMO2 cathode materials for sodium-ion batteries. Issue 21 (20th May 2022) - Tong, Lu; Ma, Pengju; Shu, Jiaohong; Wang, Lili; Chen, Guanglong; Wu, Jianbao; Mi, Yiming; Zhao, Xinxin
Abstract : We studied the influences that 3d transition metals have on the cohesive energies, structural changes and operating voltages of P2-Na x MO2 during discharge based on first-principles calculations. Abstract : Layered oxide materials are regarded to be the most promising high-performance cathode materials for sodium-ion batteries owing to their high working voltage and facile synthesis. Here, we study the influences of 3d transition metals on the cohesive energies, structural changes and operating voltages of P2-Na x MO2 during discharge based on first-principles calculations. Our results confirm that the performances of P2-Na x MO2 are associated with the chemical properties of the transition metals. In addition to this, we disclose that the involved orbitals of the 3d transition metal also greatly impact the electrochemical performance of the P2-Na x MO2 material during discharge according to the analysis of electronic structures. The jumps in the working voltage and volume during discharge are closely related to the occupation of the eg and t2g orbitals. Therefore, it is necessary to ensure that the discharge or charge process is carried out in one degenerate orbital to avoid jumps in the voltage and volume of the material. Our results could shed a light on the subsequent design of layered oxide cathodes with high cycle stability and a smooth voltage curve.